Legal Adaptation to Smart Contract Agreements in Indonesia: Navigating Digital Disruption in Business Contracts - Delfina, Dinda (Ilomata International Journal of Social Science, 2025)
This study aims to: (1) examine the legal aspects of smart contracts in the Indonesian legal system and propose adaptations to existing laws and regulations to suit the characteristics of smart contract technology; (2) identify normative and implementative challenges in the legal adaptation process, such as normative gaps and the lack of a standard framework; and (3) formulate the direction of legal reform needed to form responsive and contextual smart contract regulations. Unlike previous studies which are generally descriptive and technological in nature, this study provides a legal contribution by mapping gaps in national contract law and presenting a comparative analysis as a basis for formulating a smart contract regulation model in Indonesia. This research uses a juridical-normative and empirical-qualitative approach, with a doctrinal legal analysis of the legislation, legal literature study, and in-depth interviews with legal practitioners and technology actors. The main findings of this research indicate that there is no legal framework that explicitly regulates the validity and execution of smart contracts, which creates legal uncertainty. Therefore, it is recommended that the principle of freedom of contract in the Civil Code be expanded to include digital contracts that are executed automatically. In addition, special regulations are needed in the form of derivative regulations or technical guidelines that bridge blockchain technology with national civil law principles. The practical contribution of this research is to provide a starting point for policymakers and academics in designing smart contract regulations in Indonesia that are comprehensive and responsive to technological developments, so that they can provide legal certainty while supporting digital innovation.